Processing chocolate milk drink by low-pressure cold plasma technology. (25th April 2019) - Coutinho, Nathalia M.; Silveira, Marcello R.; Fernandes, Leonardo M.; Moraes, Jeremias; Pimentel, Tatiana C.; Freitas, Monica Q.; Silva, Marcia C.; Raices, Renata S.L.; Ranadheera, C. Senaka; Borges, Fábio O.; Neto, Roberto P.C.; Tavares, Maria Inês B.; et al.
Highlights: Chocolate milk drink manufactured using cold plasma technology. All the operational conditions improved pH values. Milder and more severe operational conditions decreased total phenolic content, ACE values and volatile compounds. Milder and more severe operational conditions proportionated less favorable health fatty acid indexes. Abstract: This study aimed to evaluate the effect of the process time (5, 10, and 15 min) and flow rate (10, 20, and 30 mL/min) of cold plasma technology on physio-chemical characteristics (pH), bioactive compounds (DPPD, Total Phenolic Compounds, ACE-inhibitory activity values), fatty acid composition, and volatile compounds profile of chocolate milk drink. The mild (lower flow rate and process time) and more severe (higher flow rate and process time) conditions led to a reduction of the bioactive compounds (total phenolic compounds and ACE-inhibitory activity), changes in fatty acid composition (increased saturated fatty acid and decreased monounsaturated fatty acid and polyunsaturated fatty acid), less favorable health indices (higher atherogenic, thrombogenic and hypercholesterolemic saturated fatty acids and lower desired fatty acids), and lower number of volatile compounds. In contrast, in intermediate cold plasma conditions, an adequate concentration of bioactive compounds, fatty acid composition, and health indices, and increased number of volatile compounds (ketones, esters, and lactones) were observed. Overall, cold plasma technology has proven to be an interesting alternative to chocolate milk drinks, being of paramount importance the study of the cold plasma process parameters.